THE CONSTRUCTIONS AND ISSUES OF MOTHERHOOD: AN ANALYSIS OF INTAN PARAMADITHA'S SHORT STORY COMPILATION ENTITLED"SIHIR PEREMPUAN" - Husnul Hanifah, - (2011)
This paper is the study of motherhood in Intan Paramaditha's short story compilation. The purpose of this study is to reveal the constructions and issues of motherhood through the analysis of characters, expressions and events on the texts. In addition, Feminist Literary Criticism was applied in the study to analyze the construction as well as the issues of motherhood raised on the texts. The result of the analysis underlines three major points: first, motherhood can be constructed through the ways the mother characters are characterized; second, motherhood can be constructed through the relationship between the mother characters and their children; last, motherhood can be constructed through the ways the mother characters are viewed by their surroundings. Furthermore, the analysis led to another aspect of the texts, the issues of motherhood that continuously emerge. Thus, the analysis is expected to enhance the critical thinking of the researchers who conduct a similar study.